Interactions Between Carbon Metabolism and Photosynthetic Electron Transport in a Chlamydomonas reinhardtii Mutant Without CO2 Fixation by RuBisCO - Saint-Sorny, Maureen; Brzezowski, Pawel; Arrivault, Stéphanie; Alric, Jean; Johnson, Xenie (Frontiers in Plant Science, 2022)
A Chlamydomonas reinhardtii RuBisCO-less mutant, ΔrbcL, was used to study carbohydrate metabolism without fixation of atmospheric carbon. The ΔrbcL mutant shows a remarkable ability to sustain photosynthetic electron transport via oxygen photo-reduction. We have compared ΔrbcL in the absence and presence of acetate and have correlated the kinetics of the primary carbon metabolites to chlorophyll fluorescence induction curves to better understand the regulation of photosynthetic control mechanisms. We identify that in the absence of acetate, ΔrbcL photosynthetic electron transfer reactions generate ATP and carbon metabolism responds to the light, as observed for Calvin Benson Bassham (CBB) cycle intermediates. Indeed, ribulose 1,5-bisphosphate (RuBP), the last intermediate before carboxylation by RuBisCO, accumulates significantly with time, whereas CBB cycle intermediates for RuBP regeneration, dihydroxyacetone phosphate (DHAP), pentoses phosphates and ribose-5-phosphate (R5P) are rapidly accumulated in the first seconds of illumination, then consumed, showing that although the CBB is blocked, the other enzymes are still transiently active. In opposition, in the presence of acetate, consumption of CBB cycle intermediates is strongly diminished, suggesting that the link between light and primary carbon metabolism is almost lost. Phosphorylated hexoses show a tendency to accumulate in the light and starch is significantly accumulated. In this case, the presence of reduced carbon results in heterotrophic metabolism dominating with glyoxylate and tricarboxylic acid (TCA) cycle intermediates being the most highly represented metabolites, specifically succinate and malate.